2021
DOI: 10.3390/app11198936
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and Analysis of the Results of Non-Contact Methods in Determining the Vertical Displacements of Timber Beams

Abstract: Determining the displacements and consequent deformations of structures is a demanding branch of engineering. Displacements are most often determined by geodetic methods, among which high-precision non-contact methods have recently taken the lead. Engineering geodesy is an indispensable part of construction projects. In the desire for efficient and fast measurements, the technology of terrestrial laser scanning (TLS) and the use of robotic total station (RTS) and other geodetic methods are becoming more and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Further, rigorous deformation analysis and tests of significance of the results are missing [12,13]. Tests in laboratory conditions of the latest generation of laser scanners have concluded that the laser scanner can be used to detect vertical displacement non-natural targets marked with photogrammetry markers with millimeter accuracy [14]. Image analysis techniques, in contrast, are very sensible for identifying displacements in transverse direction.…”
Section: Introductionmentioning
confidence: 99%
“…Further, rigorous deformation analysis and tests of significance of the results are missing [12,13]. Tests in laboratory conditions of the latest generation of laser scanners have concluded that the laser scanner can be used to detect vertical displacement non-natural targets marked with photogrammetry markers with millimeter accuracy [14]. Image analysis techniques, in contrast, are very sensible for identifying displacements in transverse direction.…”
Section: Introductionmentioning
confidence: 99%